Evaluation on thermal and mechanical performance of the hot tank in the two-tank molten salt heat storage system. (25th February 2020) - Wan, Zhenjie; Wei, Jinjia; Qaisrani, Mumtaz A.; Fang, Jiabin; Tu, Nan
Highlights: The heat loss nature of the tank is revealed. Stiffnesses of the ring wall should be above 30 MPa/m. Stiffnesses of the tank foundation fillers should be above 5 MPa/m. Adequate gap space between the tank wall and the insolation should be guaranteed. The working temperature should be used when designing a heat storage system. Abstract: A few tank failure accidents in the concentrated solar power plant have occurred in recent years, resulting in huge economic losses. In the present study, thermal and mechanical performance of the molten salt (60% NaNO3 and 40% KNO3 ) heat storage tank were studied. A coupled thermal performance evaluation model was proposed to evaluate heat losses and temperature distributions of the tank. The finite element method was then adopted to investigate the mechanical performances of the tank under different working conditions. The results indicated that the radiation in the inner air space of the tank made the temperature of the tank roof equal to that of the salt, so the temperatures of the tank wall remained constant at different salt levels. This eventually led to a constant heat loss of the tank at different salt levels. The temperature of the tank foundation was very high and greatly non-uniform, so a cooling system for the tank foundation was necessary for the safety of the tank operation, and the flow direction of the cooling air should be from the tank center to the outer part for obtaining a uniform temperature in the radial direction of the tank. With a rigid tank foundation, the range of the total stress is about 100 MPa for a daily charging/discharging cycle operation which may result in the fatigue in the tank shell. Lower foundation stiffness reduces the total stress range which in turn reduces thermal fatigue, but the stiffness of the ring wall and the tank foundation fillers should be above 30 MPa/m and 5 MPa/m respectively for a safe settlement and stress state. The thermal deformation in the tank is very high (e.g. 113.6 mm for the hot tank in the Solar Two system), and a small restriction of thermal deformation can lead to extremely high thermal stress which is detrimental for the safety of an operating tank, so any restriction in the thermal deformation should not be allowed.